Brief emotional eating scale: A multinational study of factor structure, validity, and invariance. (1st June 2023) - Ruiz, Montse C.; Devonport, Tracey J.; Chen-Wilson, Chao-Hwa (Josephine); Nicholls, Wendy; Cagas, Jonathan Y.; Fernandez-Montalvo, Javier; Choi, Youngjun; Gan, Yiqun; Robazza, Claudio
Abstract: Emotional eating or the tendency to eat in response to emotional states can be assessed using self-report measures. The Emotional Eating Scale-II is a commonly used and reliable instrument that measures the desire to eat in response to a range of unpleasant and pleasant emotions. The current study aimed to corroborate the validity of the EES-II and expand its utility by investigating its dimensionality and testing its measurement invariance in samples from English-speaking and non-English-speaking countries. Convergent and predictive validity in respect of food craving, eating, and health indicators were also examined. This cross-national study included a total of 2485 adult participants recruited from Finland, North America, Philippines, United Kingdom, China, Italy, Spain, and South Korea, who completed the EES-II in six different languages. Factor analyses supported a four-factor structure including valence (pleasant, unpleasant) and activation (high, low) for a 12-item English version and slightly modified non-English adaptations. The model exhibited good fit in all samples, and convergent validity was demonstrated. Full invariance of factor loadings and partial invariance of factor loading, intercepts, and error variances was established across samples. Structural equation models revealed that high activation (pleasant and unpleasant) states predicted food cravings and reported eating. Overall findings across multiple samples and countries supported the factorial structure, reliability, invariance, and validity of the resulting Brief Emotional Eating Scale (BEES).